Az Északnyugat-Dunántúl térségének gazdasági adottságai és versenyelőnyei - Rechnitzer, János (Tér és Társadalom, 1997)
The essay analyses the economic conditions of a region comprising four counties, Győr-Moson-Sopron, Vas, Veszprém and Zala, trying to explore the common features of them and the possible regional particularities in the economic structure. The region as a whole is in a favourable position in the Hungarian modernisation, although it is not homogeneous but divided. The author demonstrates, with the appearance of the businesses, the significant regional differences behind the above national average development dynamics of the region. In Győr-Moson-Sopron county mainly capital intensive businesses settled down, while in the other counties those organisations which need less investments, rather business will and initiatives. The structure of the region is not homogeneous with respect to the economic capacity, either. The region along the Hungarian border with Austria is the main attraction for foreign inward investment, escorted by a zone from the State border to Győr and the more and more spectacular development zone between Győr and Sopron. The third growth axis is along Lake Balaton where tourism is the dominant sector. The fourth new development zone is the axis between the towns of Veszprém and Ajka, which is more and more organically connected to the other centre of the Hungarian modernisation, Székesfehérvár (which is already out of the region). In the renewal of the economic structure, the role of the foreign capital is decisive, as 46.9% of the organisations and 40.9% of the capital assets in the Hungarian countryside are in this region, which means that 23.8% of foreign inward investments in Hungary was realised in Nortwest Transdanubia (1994). The biggest investor was Germany, followed by Austria with smaller scale but several investments. Foreign interest can be found all through the economy, its role has become dominant in all sectors by now. The foreign economic connection of the region is also determined by foreign investments: The growing volume of exports to and imports from Germany characterise the direction of the economic links, at the same time the number of cooperations with Austria has been declining. A new orientation of the economy of the region is towards Italy, especially in import relations. In the employment structure of the region the proportion of industry is still dominant, but in some counties we can see a moderate increase in the share of the service sector. The proportion of the employees in modern business services is not high (3-3.2%), indicating that although these activities are present in the economies of the counties, they are not significant. Among the economic organisations of the region the proportion of those whose activity is in economic and business services is high (17.9%), it does not mean, however, that their performance is significant. The unemployment rate is below the national average in the regíon, in fact, it is still decreasing (in Zala and Veszprém) or stagnating at a low levei (Győr-Moson- Sopron and Vas). This indicates that only the first two counties have considerable employment reserves. The essay examines the region and its counties in a national comparison. The competitiveness of the region is evaluated by the economic performance, the development possibilities and the location factors. By the indices worked out for the analysis, this region is in a relatively favourable position by Hungarian standards, in fact, we can say that its competitiveness is excellent. The performance of the economy, characterised by the volume of GDP, the dynamics of investments, unemployment and the volume of industrial export, is the best in Hungary in Győr- Moson-Sopron and Vas counties, and is also good in the other two counties. The development possibilities were evaluated by several groups of factors, i.e. the tertiary economy, business and capital activity and innovation potential. The economic performance and business and capital activity of Nortwest Transdanubia lags behind its innovation potential, i.e. the resources for internal renewal are limited, the external economic-development dependence of the region is high, so to say dominant. The location factors were analysed by 34 factors in 8 groups. We can draw the conclusion that the whole of the region is in a favourable situation by Hungarian standards, at the same time it is divided and does not show a homogeneous picture. Finally the essay states that the pace of economic modernisation is faster in this region than in other parts of Hungary, but the signs of regional organisation are not yet visible. The direction of the future developments is in local economic development, but the strengthening of the regional connections of the economic base in different directions is also necessary.